Nice Guys Finish First: The Competitive Altruism Hypothesis - L. Hardy, Charlotte (ProQuest Dissertations & Theses, 2007)
Altruism, the intention to benefit others at a cost to oneself, is one of the major puzzles in the behavioural sciences today. A review of the literature in Chapter 2 revealed that, over the past decades, two main evolutionary models of altruism have emerged, kin selection theory and reciprocal altruism theory. These models are wellfounded in mathematical theory and they have received a lot of empirical support, yet questions remain about the extent to which they can fully account for the diversity and ubiquity of altruistic patterns in human society.The aim of this thesis was to present and empirically test a novel theory of altruism, called competitive altruism, which I proposed may account for a range of altruistic behaviours among humans in particular, that the theories of kinship and reciprocity cannot easily explain. Competitive altruism is the process through which individuals attempt to outcompete each other in terms of generosity. It emerges because altruism enhances the status and reputation of the giver. Status, in turn, yields benefits that would be otherwise unattainable. The empirical chapters presented nine experimental studies that tested these various aspects of the competitive altruism hypothesis in small groups involved in a public good dilemma, a task that pits altruistic and selfish motives against each other.In Chapter 3, the first of these experiments revealed that in a reputation environment when contributions were public, people were more altruistic. The most altruistic members gained the highest status in their group, and were most frequently preferred as cooperative interaction partners.Chapter 4 presented two experiments, showing that, in a reputation environment, public good contributions increase even if these goods are already provided by others (Study 4) or are simply unattainable (Study 5). Wasteful contributions increased the status of the giver, suggesting that non-strategic generosity and cooperation have great signalling power.Chapter 5 showed that high status members behave more altruistically than low status members. Furthermore, a rise in social status during a group task increases altruism, whereas a loss in status decreases altruism (Study 7). These results support the idea that by behaving altruistically group members “compete” for social status within their group.Chapter 6 presented two studies that examined the status and reputation of those who engage in altruistic behaviour, for example, through contributions to public goods. Study 8 reports that high status occupations in British society are perceived to be those that involve contributing altruistically towards the community. Study 9 uses historical data and provides support for the hypothesis that altruistic contributions to three specific public goods can earn people their reputations.The main conclusion drawn in Chapter 7, is that competitive altruism may provide a new way of thinking about human sociality. It helps to explain why humans are unusually altruistic and cooperative even (or especially) when they operate in large groups. Implications and limitations of the findings and ideas for future research from competitive altruism were also discussed.